COVID-19 and common mental health symptoms in the early phase of the pandemic: An umbrella review of the evidence. - Anke B Witteveen; Susanne Y Young; Pim Cuijpers; José Luis Ayuso-Mateos; Corrado Barbui; Federico Bertolini; Maria Cabello; Camilla Cadorin; Naomi Downes; Daniele Franzoi; Michael Gasior; Brandon Gray; et al. (PLoS Medicine)
Background There remains uncertainty about the impact of the Coronavirus Disease 2019 (COVID-19) pandemic on mental health. This umbrella review provides a comprehensive overview of the association between the pandemic and common mental disorders. We qualitatively summarized evidence from reviews with meta-analyses of individual study-data in the general population, healthcare workers, and specific at-risk populations. Methods and findings A systematic search was carried out in 5 databases for peer-reviewed systematic reviews with meta-analyses of prevalence of depression, anxiety, and post-traumatic stress disorder (PTSD) symptoms during the pandemic published between December 31, 2019 until August 12, 2022. We identified 123 reviews of which 7 provided standardized mean differences (SMDs) either from longitudinal pre- to during pandemic study-data or from cross-sectional study-data compared to matched pre-pandemic data. Methodological quality rated with the Assessment of Multiple Systematic Reviews checklist scores (AMSTAR 2) instrument was generally low to moderate. Small but significant increases of depression, anxiety, and/or general mental health symptoms were reported in the general population, in people with preexisting physical health conditions, and in children (3 reviews; SMDs ranged from 0.11 to 0.28). Mental health and depression symptoms significantly increased during periods of social restrictions (1 review; SMDs of 0.41 and 0.83, respectively) but anxiety symptoms did not (SMD: 0.26). Increases of depression symptoms were generally larger and longer-lasting during the pandemic (3 reviews; SMDs depression ranged from 0.16 to 0.23) than those of anxiety (2 reviews: SMDs 0.12 and 0.18). Females showed a significantly larger increase in anxiety symptoms than males (1 review: SMD 0.15). In healthcare workers, people with preexisting mental disorders, any patient group, children and adolescents, and in students, no significant differences from pre- to during pandemic were found (2 reviews; SMD's ranging from -0.16 to 0.48). In 116 reviews pooled cross-sectional prevalence rates of depression, anxiety, and PTSD symptoms ranged from 9% to 48% across populations. Although heterogeneity between studies was high and largely unexplained, assessment tools and cut-offs used, age, sex or gender, and COVID-19 exposure factors were found to be moderators in some reviews. The major limitations are the inability to quantify and explain the high heterogeneity across reviews included and the shortage of within-person data from multiple longitudinal studies. Conclusions A small but consistent deterioration of mental health and particularly depression during early pandemic and during social restrictions has been found in the general population and in people with chronic somatic disorders. Also, associations between mental health and the pandemic were stronger in females and younger age groups than in others. Explanatory individual-level, COVID-19 exposure, and time-course factors were scarce and showed inconsistencies across reviews. For policy and research, repeated assessments of mental health in population panels including vulnerable individuals are recommended to respond to current and future health crises.